Determination of Time Savings for Passengers by Applying the Public Passenger Transport Preference in Cities - Jozef Gnap; Jana Kupculjakova; Stefania Semanova (Communications - Scientific letters of the University of Zilina, 2018)
The paper deals with the issue of delays of public transport vehicles at the signal controlled junctions. Based on the road traffic survey results, the average values of vehicle delays were determined. By using those values, it is possible to define time savings for the vehicles and mainly for passengers that are transported. The time savings were determined based on the relationships and coefficients defined in this paper.